Vol. 3, No. 1, September 2021 - Bodhy Widodo (Scientia Regendi, 2021)
Indonesia as a sovereign state recognizes the existence of human rights (HAM) in Article 28 E paragraph (3) of the 1945 Constitution of the Republic of Indonesia (UUD 1945), which reads: "Everyone has the right to freedom of association, assembly and expression. ". The Indonesian government has regulated the freedom to express opinions in public as stated in the Law of the Republic of Indonesia Number 9 of 1998 concerning Freedom to Express Opinions in Public. One of the ways to implement freedom of expression in public based on Article 9 paragraph (1) of the Law on Freedom of Expressing Opinions in Public, is through demonstrations or demonstrations. This demonstration is usually carried out to support or reject a policy issued by the government or private sector. Based on the results of the author's research, the process of law enforcement against perpetrators of anarchist demonstrations by the Police still has obstacles, namely that the law enforcers when enforcing the law with repressive actions are still referred to as human rights violations, arrogant police, etc. because according to anarchist protesters the freedom to express opinions in public is protected by law. The role of the police has three stages, namely pre-emptive, preventive and repressive. The three things that are most dominantly carried out by the police are persuasive and preventive, in other words, the approach is in the form of negotiation, however repressive actions can be taken if the escalation of protesters has led to illegal acts. : There is that every member of the police is less able to control his emotions towards the situation that has flared up due to protests. Lack of professionalism of the police in handling protests. In addition, the field conditions are different from the theoretical conditions that make it difficult for the police to secure protesters. The protesters think that if the police secure one of them who are anarchist, they think that the police have arrested them even though this was done to curb the demonstration. society tends to be negative so that every police action is considered wrong